Prediction of postoperative liver failure using gadoxetic acid‐enhanced magnetic resonance imaging in patients with hepatocellular carcinoma. Issue 7 (27th July 2016) - Jin, Young‐Joo; Lee, Seung Ho; Cho, Soon Gu; Kim, Jun Ho; Lee, Jin‐Woo; Lee, Kun Young; Shin, Woo Young
Abstract: Background: We intended to determine the usefulness of gadoxetic acid‐enhanced magnetic resonance (MR) imaging on preoperative prediction of the risk of postoperative liver failure (PLF) using measurement of relative liver enhancement (RLE) in patients who underwent surgical resection of hepatocellular carcinoma (HCC). Methods: A total of 121 HCC patients who had underwent gadoxetic acid‐enhanced MRI before surgery between January 2012 and April 2015 at our hospital was retrospectively analyzed. RLE was calculated as the ratio of signal intensity measurements of the liver parenchyma in each liver segment before and 20 min after intravenous administration of gadoxetic acid. PLF was defined based on the "50–50 criteria" (prothrombin time <50% and serum bilirubin >5 mg/dL on 5 days after surgery). Results: Of the 121 patients, 74 (61.2%) patients had liver cirrhosis, clinically. Median tumor size 2.8 cm (range, 1–14 cm), 106 (87.6%) patients had a single HCC, and 101 (83.5%) patients had HCC within Milan criteria. Based on the "50–50 criteria", PLF was observed in 7 (5.8%) patients. Mean RLE was significantly lower in patients with PLF than those without it (55.9% vs 85.5%, P < 0.01). In a multivariate analysis, decreased RLE was a significant independent risk factor for PLF in HCC patients (odds ratio 0.97, P = 0.03). Optimal cut‐off RLE value was 82.36. Conclusions: RLE was significantly lower in patients with PLF than those without it. Measurement of RLE using gadoxetic acid‐enhanced MR imaging before surgery can be useful for prediction of PLF in HCC patients who receive surgical treatment.